Yunnan Baiyao Might Mitigate Periodontitis Bone Destruction by Inhibiting Autophagy and Promoting Osteoblast Differentiation in vivo, ex vivo and in vitro - Liu W; Li Y; An Y; Zhao R; Wei C; Ren X; He H (Journal of Inflammation Research, 2024)
Wang Liu,1,2,* Yanjie Li,1,2,* Yuanyuan An,1,2 Ruoyu Zhao,1,2 Chenxi Wei,1,2 Xiaobin Ren,1 Hongbing He1 1Department of Periodontology, Kunming Medical University School and Hospital of Stomatology, Kunming, 650106, People’s Republic of China; 2Yunnan Key Laboratory of Stomatology, Kunming, 650106, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongbing He; Xiaobin Ren, Department of Periodontology, Kunming Medical University School and Hospital of Stomatology, Kunming, 650106, People’s Republic of China, Tel +8613987196646 ; +8615877930860, Email hehongbing@kmmu.edu.cn; Renxiaobin6688@163.comBackground and Objective: Periodontitis is an inflammatory disease that eventually destroys tooth-supporting tissue. Yunnan Baiyao (YNBY), a traditional Chinese medicine compound with haemostatic and anti-inflammatory properties has shown therapeutic potential in several diseases. Our previous study revealed that YNBY suppressed osteoclast differentiation in periodontitis. The purpose of this study is to investigate the influences of YNBY on osteoblasts and explore its potential mechanisms.Materials and Methods: A rat periodontitis model was established by ligation of maxillary second molars. After the end of modelling, histopathological observation by hematoxylin-eosin (HE) staining and Masson trichrome staining, detection of bone resorption by Micro-CT scanning, detection of osteoclasts by tartrate-resistant acid phosphatase (TRAP) staining, expression of osteocalcin (OCN) and microtubule-associated protein 1 light chain 3 (LC3) by immunohistochemistry. Lipopolysaccharides was used to irritate MC3T3-E1 osteoblastic cells and ex vivo calvarial organ as an in vitro model of inflammation. CCK-8 assay was performed to examine the toxicity of YNBY to MC3T3-E1 osteoblastic cells. Osteogenesis was assessed with alizarin red staining, immunofluorescence staining, Western blot and immunohistochemical staining. Transmission electron microscopy, fluorescent double staining, Western blot and immunohistochemical staining were employed to detect autophagy.Results: Histological and micro-CT analyses revealed that YNBY gavage reduced bone loss caused by experimental periodontitis and upregulated osteogenic proteins in vivo. YNBY attenuated the production of autophagy-related proteins in periodontitis rats. Additionally, YNBY promoted osteogenesis by inhibiting inflammation-induced autophagy in vitro. Furthermore, YNBY suppressed LPS-mediated bone resorption and promoted the production of osteoblast-related proteins in inflamed calvarial tissues ex vivo.Conclusion: This study demonstrated, through in vivo, in vitro and ex vivo experiments, that YNBY promoted osteoblast differentiation by suppressing autophagy, which markedly alleviated bone destruction caused by periodontitis.Keywords: Yunnan Baiyao, periodontitis, osteoblasts, autophagy